Cooking and Eating Quality Profiling of Some Popular Rice Cultivars In Bangladesh - Saika Anne; Md. Anwarul Haque; Sharif Ar Raffi (Agricultural Science, 2019)
Eating and cooking quality of rice plays major role in consumer’s preference for any cultivar. In the present investigation 21 popular rice cultivars were analyzed for their cooking and eating quality traits. Moderate variations were observed for all the traits studied except solid in cooking water. Among the cultivars, cooking time ranged from 14.02 to 21.37 minutes, water uptake ratio from 2.24 to 3.324 %, solid in cooking water from 1.027 to 1.049 gm, volume expansion ratio from 2.8 to 4.28 %, % amylose content from 17.367 (low) to 27.387(intermediate), protein content from 6.28 to 8.96 (%), and most of the cultivars were found with intermediate gelatinization temperature. Solid in cooking water was found positively correlated with cooking time, but negatively with water uptake ratio. Considering the preferences for cooked rice, high amylose content and low to intermediate gelatinization temperature of BRRI rice29, BRRI rice49 and Binarice-11 justified their popularity among the farmers and consumers.